The Application of Silviculture Techniques on White Jabon (Neolamarckia cadamba Miq) by The Farmers of Community Forest in Konawe Regency, Southeast Sulawesi - Husna; Inggrik Valentin Rare; Asrianti Arif; Albasri; Tuheteru, Faisal Danu (Talenta Publisher, 2019)
This study aimed to determine the silvicultural techniques that applied by four farmers in private forest of white jabon and to know the growth of white jabon in Konawe. This study was conducted at four locations namely Sub District of Unaaha District of Unaaha, Wawoone Village, Tetemotaha Village and Langgonawe Village of Wonggeduku District, Konawe, Southeast Sulawesi Province. This study took place from May until October 2016, and was carried out in three phases namely choice of location, interviews with owners and Jabon stand inventory. The results showed that farmers in Konawe was planting white Jabon (Neolamarckia cadamba Miq.) without Jabon silvicultural techniques, special training. The farmers’s knowledge cultivating through books, Internet access and other farmers. Silvicultural techniques which applied by farmers were included seedlings originating, land preparation, planting, and maintenance included replanting, weeding, fertilizing, pest and disease control and thinning.